User Association and Power Allocation in Multi-Connectivity Enabled Millimeter-Wave Networks With Limited Backhaul - Miaofeng Wang; Junyuan Wang; Yuan Kai; Funing Xia; Xiankun Zeng; Fuqiang Liu (IEEE Open Journal of the Communications Society, 2023)
Millimeter-wave (mmWave) communication has been recognized as a key technology to improve the rate performance of the next-generation wireless networks. However, the mmWave signals suffer from severe path loss and penetration attenuation due to the extremely high frequency characteristics. As a result, a massive number of small base stations (SBSs) would be deployed in mmWave networks to provide seamless coverage. To overcome obstacle blockages, the multi-connectivity technology that enables a user to associate with multiple SBSs simultaneously has been proposed by 3GPP, which brings new challenges to resource allocation. This paper investigates the joint user association and power allocation problem in such a multi-connectivity enabled mmWave network aiming at maximizing the system sum rate while considering the backhaul capacity limit and users’ individual rate requirements. The optimization problem is highly non-convex and NP-hard to solve. By decoupling it into user association subproblem and power allocation subproblem, we first propose a novel swapping algorithm on top of the classic many-to-many matching scheme to perform user association, and then apply the difference of convex functions (D.C.) programming approach to transform the non-convex power allocation subproblem into a convex one and solve it by an iterative algorithm. Simulation results demonstrate the superior performance of the proposed multi-connectivity user association and power allocation schemes over the existing ones.